POLYSEMIC TERMS IN CHINESE,GERMAN, GREEK AND POLISH LEGAL LANGUAGE. A COMPARATIVE STUDY - GORTYCH-MICHALAK, Karolina; GRZYBEK, Joanna (Comparative Legilinguistics, 2013)
The main issue of the paper is the phenomenon of polysemy, which is present in the Chinese, German, Greek and Polish legal languages. The phenomenon is seen as the criterion of comparative studies between the specified legal languages. As polysemy is often discussed together with homonymy, the authors have decided to define polysemy in the introduction of the text, on the basis of etymology and being contrary to homonymy. The first assumption is an existence of the polysemy of certain terms (words and syntagmas), which relies on simultaneous existence of the term both in general (lay) language and in language for special purposes. The LSP may be the legal language, for example. Based on the existing research of legal language, the authors assume polysemy does not have a homogenous character as a term and moreover this is confirmed by various legilinguistic classifications. There are typologies of legal language based on the criterion of source text, but the authors also propose the consideration of a classification performed on the basis of various fields of law i.e. civil law, constitutional law, criminal law together with confirmation of classification. This criterion may be very useful when explaining the polysemy of legal terms as it originates not only from different types of legal texts, but primarily comes from legal fields. The performed comparative analysis of selected legal terms of different Chinese, German, Greek and Polish legal fields indicates that the multiplicity of meanings of the same term (word/syntagma) comes from the presence of this term in different legal fields. Simultaneously, the primarily assumed statement of the existence of polysemy in the frame of a certain language for special purposes, i.e. legal language, is confirmed. This assumption may be a valuable aspect of further research of national legal languages and may be useful for the users of legal language such as legal translators or legal comparatists.